THE USE OF ONLINE MEDIA AND TOPOGRAPHY MAP IN THE TOPIC OF LANDSLIDE NATURAL DISASTER, ADVANCED EARTH PHYSICS COURSE - Nur Islami (International Journal of Educational Best Practices, 2019)
Advanced Earth Physics course is one of the courses discusses all aspects of physics that exist in natural processes occurring on the earth. One of the topics discussed was Landslide Natural Disaster. The purpose of this study is to discuss the use of online media and topography map in Advance earth physics classes to analyse the location of possible landslides. This research was conducted on students who are taking advanced earth physics courses for the even semester in the University of Riau, Physics Education Study Program, and 20182019 academic year. Students were given the concept of a landslide and guidelines for using Google Earth and on how to produce the topography map. Then students were required to do a mini project in terms of using Google Earth and Topography Map and to analyse the possibility of a landslide zone. Subsequently, students were given a questionnaire about understanding the material of the Avalanche that was studied with the help of Google Earth and topography map. The results show that almost all students fully understand and like what they are doing, as evidenced by an average score of 3.78 (scale 4) in terms of Google Earth's utility in studying landslide zones. Thus it can be concluded that the Google Earth media is very well-liked and can provide a deeper understanding to students in learning the concept of Landslide Natural Disasters in Advanced Earth Physics courses.